PENGARUH DISIPLIN KERJA DAN PENGALAMAN KERJA TER-HADAP PRESTASI KERJA PERAWAT (STUDI PERAWAT PADA RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU) - Fitria Sahidatulhasana; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of work discipline and work experience on nurses' work performance in the Rumah Sakit Jiwa Tampan partially and simultaneously. This study used a questionnaire as a data collection tool that was distributed to 61 respondents at the Tampan Mental Hospital of Riau Province. The data are then processed using descriptive analysis and statistical analysis using SPSS 21.0 by conducting validity, reliability testing, simple linear regression analysis, multiple linear analysis, determination analysis (R2) and hypothesis testing with t test (partial test) and F test (simultaneous ).               The results showed that the first hypothesis testing is work discipline on nurse work performance that is tcount (6.436)> t table (2.001) meaning that work discipline has a significant effect on nurse work performance. The second work experience on nurse work performance is tcount (7.879)> t table (2.001) meaning that work experience has a significant effect on nurse work performance. F test results (33.666)> F table (3.16), meaning that work discipline and work experience simultaneously have a significant effect on nurses' work performance. Keywords: Work discipline, work experience, work performance